2010
DOI: 10.1007/s11671-010-9567-4
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticulate PdZn as a Novel Catalyst for ZnO Nanowire Growth

Abstract: ZnO nanowires have been grown by chemical vapour deposition (CVD) using PdZn bimetallic nanoparticles to catalyse the process. Nanocatalyst particles with mean particle diameters of 2.6 ± 0.3 nm were shown to catalyse the growth process, displaying activities that compare well with those reported for sputtered systems. Since nanowire diameters are linked to catalyst morphology, the size-control we are able to exhibit during particle preparation represents an advantage over existing approaches in terms of contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Examples of such supports are high-surface-area materials such as nanoscopic or mesoporous metal oxides. These supports have previously proven to allow both the dimensional modulation of particle/oxide electronic interactions and an efficient turnover profile upon deposition in microreactor environments [26,55]. We are also further developing our previous data demonstrating the high activity of PdZn 50:50 nanoparticles in the growth of zinc oxide nanowires by chemical vapor deposition [26], hinting at further developmental potential of this bimetallic system in the controlled synthesis of semiconductor devices.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Examples of such supports are high-surface-area materials such as nanoscopic or mesoporous metal oxides. These supports have previously proven to allow both the dimensional modulation of particle/oxide electronic interactions and an efficient turnover profile upon deposition in microreactor environments [26,55]. We are also further developing our previous data demonstrating the high activity of PdZn 50:50 nanoparticles in the growth of zinc oxide nanowires by chemical vapor deposition [26], hinting at further developmental potential of this bimetallic system in the controlled synthesis of semiconductor devices.…”
Section: Discussionsupporting
confidence: 61%
“…We have previously reported the synthesis of a range of PdZn nanoparticles, with a variety of molar ratios, via liquidtype reduction and the preliminary monitoring of their catalytic properties in both phenylacetylene semihydrogenation [25] and the growth of ZnO nanowires [26], where a 50:50 nominal metal ratio has proven highly active. We now report an extended structural study of PdZn particulates over a full compositional range.…”
Section: Introductionmentioning
confidence: 99%
“…showing the feasibility of methanol steam reforming (MSR) at millisecond contact time, high conversion and low temperature over ZnPd compared to other fuels [13;14] . Besides being studied as catalyst in methanol steam reforming, the intermetallic compound ZnPd supported on ZnO is also a hydrogenation catalyst [15][16][17][18][19][20][21][22][23][24][25][26][27] , active in the reverse-water-gas-shift reaction [28][29][30] , the partial oxidation of methanol [31][32][33] , the steam reforming of ethanol [34] , the hydroformylation of ethylene [16] , the oxidative acetoxylation [35;36] , the esterification [37] and can be used as catalyst to grow ZnO nanorods [38] . General information about intermetallic compounds in catalysis can be found in a recent review [39] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that a catalyst–cocatalyst system offers synergistic or complementary effects to promote the controllable growth of 1D nanostructures, especially 1D carbon nanomaterials. Using the polymer template approach to incorporate a variety of metal species, a catalyst–cocatalyst system in which ZnO is catalyst and metal oxides such as SnO, Ga 2 O 3 , CuO, Y 2 O 3 , and Fe 2 O 3 are cocatalysts can be prepared.…”
Section: Resultsmentioning
confidence: 99%